Analisis Keterampilan Dasar Mengajar Guru untuk Meningkatkan Hasil Belajar Siswa di UPTD SD Negeri Pailelang - Greace C. Jalla; Jon A. Lalang Yame; Franselia P. Fanmaley; Altim A. Dolu; Benyamin Mabilehi; Agustina Penikai (Concept: Journal of Social Humanities and Education, 2024)
This research aims to examine the influence of teachers' teaching skills on student learning outcomes in elementary schools. This research will specifically examine teaching skills and learning readiness as factors that can influence student learning outcomes. Teachers' teaching skills are very important in the learning process because it is one way teachers can do it so that the learning process in the classroom fosters effective student learning activities and learning outcomes can be as appropriate as possible. what to expect. Learning activities are not enough to just listen and take notes, but must be more complex than that. This shows that the teacher's teaching skills must be able to enable students to stimulate various learning activities. In writing this article, we used a qualitative approach with a literature study based on several scientific journals, electronic books and other sources whose accuracy has been confirmed. The results of this study describe that there is an influence of teacher teaching skills on student learning outcomes in elementary schools. By mastering basic teaching skills, teachers can distribute all learning materials so as to achieve the learning objectives themselves